Secular and Theological Ethics: A Brief Overview (Philosophy and Progress, 2024)
Ethics is a study which deals fundamentally with the rules of conduct from moral point of view. The main characteristic of ethics is to judge the value of moral act or moral conduct. Therefore, ethics means a code of conduct. The history of the development of morality grew through a long process of evolution of certain morality like ‘taboos’, habits and customs in the primitive society. There are two broad divisions of ethics i. e., secular ethics and theological ethics. The history of the development of secular ethics flourished through four periods i. e., the Greek ethics, the Medieval ethics, the Modern ethics and the Contemporary ethics. Each period has its own prominent characteristics. Moreover, the history of theological ethics grew with the rise of different religions like Islam, Christianity, Judaism, Hinduism and Buddhism. Morality has been developed during the period of more than two thousand years. Within this long span of time, many doctrines, ideas and values are included in it. Hence, morality takes different shapes in different periods and ethical views also develop accordingly. In this article, an attempt has been made to show a gradual development of morality- secular and theological. Again, the similarities and the dissimilarities between secular and theological ethics are the additional concerns of this paper.Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 59-94